TECHNIQUES OF TRANSLATION OF CULTURAL WORD IN TOUMAWARI SURU HINA NOVEL: TEKNIK PENERJEMAHAN KOSAKATA BERMUATAN BUDAYA DALAM NOVEL TOUMAWARI SURU HINA - Tia Ristiawati; Viana Meilani Prasetio; Fitri Fauziyyah (Jurnal Kata, 2021)
Vocabulary that contains cultural elements can hardly be translated literally, so it requires proper translation techniques. By using the category of cultural word by Newmark and the translation technique by Hoed, this study aims to determine the translation technique used to translate cultural word in the novel Toumawari Suru Hina. The method used is literature study and analytical method whose results are described descriptively. Based on the results of this study, it is known that the translator of the Indonesian version of the novel uses phonological translation (20.2%), does not translated (17.6%), and footnotes (15.6%). On the other hand, the translator of the English version of the novel uses a lot of cultural equivalent techniques (18%) and descriptive translation (15.1%) to translate cultural word in the categories of material culture and social culture.